Managementâs of Construction Material Supply Chain - Syamsuir, Elvi (-)
Research on Management s of Construction Material Supply Chain in order to identify and analyze the structure of the supply chain of materials on the construction project of water resources. The expected benefits of this research is to investigate the determinants of the increase in the efficiency of the time, cost, quality and delivery of construction projects. The data used in this study are primary data interviews with Site Manager, project contractor Â and logistics object of research and secondary data obtained from the Central Office River Region V West Sumatera.Â Results of research showed a link between a good working relationship between the contractor and suppliers such as type of procurement, contract type, payment systems, and the interaction between the two companies on the effectiveness of the implementation of construction work and material supply chain management in the project